ANALYSIS OF THE IMPACT OF MEAURES' NON-TAFF POLICY ON THE PERFORMANCE OF INDONESIAN FROZEN SHRIMP EXPORTS IN MAIN DESTINATION MARKETS - Nita Aprilia; Yusman Syaukat; Faroby Falatehan (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2023)
The shrimp commodity significantly contributes to the total export value of the fisheries sub-sector in Indonesia. In 2021 Indonesia will be ranked fourth as the largest frozen shrimp exporting country in the world market. However, the value of Indonesia's frozen shrimp exports still fluctuates every year. Indonesia's frozen shrimp exports also face various challenges, from non-tariff measures (NTM) policies, incredibly sanitary and phytosanitary (SPS), and technical barriers to trade (TBT) imposed by importing countries. This study aims to analyze the performance of the Indonesian frozen shrimp trade in destination markets, the application of NTM policies by importing countries to Indonesian frozen shrimp exports, and the impact of NTM policies and other factors on Indonesian shrimp exports in destination markets. This study uses regression panel data models. The results of the study show that the performance of Indonesia's frozen shrimp export trade has a positive trend. The United States, Japan, China, the Netherlands, and France have implemented SPS and TBT policies for Indonesian frozen shrimp. The estimation results using panel data regarding the impact of NTM policies and other factors that affect the volume of Indonesian shrimp exports show that the price of frozen shrimp in the destination country has a negative effect on the volume of Indonesian frozen shrimp exports. The exchange rate and population positively affect the export volume of Indonesian frozen shrimp. Meanwhile, the SPS policy variable of the importing country has no significant effect. The TBT variable negatively and significantly impacts the export volume of Indonesian shrimp.